Low-energy ion beam bombardment of human cancer cells in vacuum to induce DNA transfection - Wongkham W. (2014)
A process of low-energy ion-beam-induced gene transfection in human cancer cells was developed for non-viral DNA transfection. The whole process included maintenance of the cells in vacuum, ion beam bombardment of the cells with optimized ion beam condition leading to a medium cell viability, and DNA transfer. A method of using a specially designed liquid-nitrogen cooled sample holder to house the cells and frozen medium to cover and protect the cells was adopted to maintain the cells viable in the vacuum condition during ion beam bombardment. Nitrogen ion beams with energy in the range 7-28 keV were used to bombard human cancer cells (HEp-2, the human laryngeal epitheloid cancer cell line) to fluence orders of 1015-1016 ions/cm2. After ion beam bombardment, the cell viability was studied. The ion beam condition which resulted in a relatively medium viability of the cells was chosen to operate ion bombardment to induce gene transfection. To the viable cells, DNA transfection using plasmid DNA pEGFPN2 was carried out. The experiment demonstrated that under appropriately controlled ion beam conditions and freezing environment, the human cells could survive and be transfected with exogenous DNA. This technique could be used as an alternative of non-viral gene transfections with a promising efficiency. © 2012 Elsevier Ltd. All rights reserved.